2003
DOI: 10.1038/sj.npp.1300178
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate Normalizes Hippocampal NPY-LI in Flinders Sensitive Line ‘Depressed’ Rats and Upregulates NPY, Galanin, and CRH-LI in the Hypothalamus: Implications for Mood-Stabilizing and Weight Loss-Inducing Effects

Abstract: Topiramate is currently used in the treatment of epilepsy, but this anticonvulsant drug has also been reported to exert mood-stabilizing effects and induce weight loss in patients. Neuropeptide Y (NPY) is abundantly and widely distributed in the mammalian central nervous system and centrally administered NPY markedly reduces pharmacologically induced seizures and induces antidepressant-like activity as well as feeding behavior. Two other peptides, galanin and corticotropin-releasing hormone (CRH), have also be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 64 publications
(84 reference statements)
0
40
0
3
Order By: Relevance
“…Topiramate has been shown to have hypothalamic effects, which could explain the reduction in appetite also recently shown in other clinical trials including diabetic patients. 19,20 The weight loss seen in the topiramate-treated group can, at least partly, explain the improved blood glucose control in these patients, although the magnitude of improvement seems considerably greater than expected for a 6.6% reduction in body weight. Animal studies indicate that the anti-hyperglycaemic effect of topiramate is independent of its effect on energy intake and/or body weight loss.…”
Section: Discussionmentioning
confidence: 90%
“…Topiramate has been shown to have hypothalamic effects, which could explain the reduction in appetite also recently shown in other clinical trials including diabetic patients. 19,20 The weight loss seen in the topiramate-treated group can, at least partly, explain the improved blood glucose control in these patients, although the magnitude of improvement seems considerably greater than expected for a 6.6% reduction in body weight. Animal studies indicate that the anti-hyperglycaemic effect of topiramate is independent of its effect on energy intake and/or body weight loss.…”
Section: Discussionmentioning
confidence: 90%
“…Animal studies suggest that central action may potentially reduce appetite and/or food intake (17,18). Studies in rodent models suggest that topiramate may also affect energy utilization, possibly due to stimulation of lipoprotein lipase in adipose tissue and skeletal muscle (19).…”
Section: Topiramate In Obese Diabetic Patientsmentioning
confidence: 99%
“…It is worth noting that drug withdrawal often precipitates symptoms of depression, and depression is a commonly observed withdrawal symptom in humans (17,18). In addition, decreased galanin expression in DRN, hippocampus, and hypothalamus have been observed in rat models of depression (19)(20)(21), and a recent clinical study reported preliminary evidence for an acute antidepressant effect of galanin (i.v.) in depressed patients (22), whereas a few early microdialysis and behavioral studies in rodents suggested depressive actions of galanin (6,8,23,24).…”
mentioning
confidence: 99%